Arnicolide D: a multi-targeted anticancer sesquiterpene lactone—preclinical efficacy and mechanistic insights - Mangalpady, Shivaprasad Shetty; Peña-Corona, Sheila I.; Borbolla-Jiménez, Fabiola; Kaverikana, Rajesh; Shetty, Shobhitha; Shet, Vinayaka Babu; Almarhoon, Zainab M.; Calina, Daniela; Leyva-Gómez, Gerardo; Sharifi-Rad, Javad (Naunyn-Schmiedeberg's archives of pharmacology, 2024)
Arnicolide D, a potent sesquiterpene lactone from Centipeda minima , has emerged as a promising anticancer candidate, demonstrating significant efficacy in inhibiting cancer cell proliferation, inducing apoptosis, and suppressing metastasis across various cancer models. This comprehensive study delves into the molecular underpinnings of Arnicolide D’s anticancer actions, emphasizing its impact on key signaling pathways such as PI3K/AKT/mTOR and STAT3, and its role in modulating cell cycle and survival mechanisms. Quantitative data from preclinical studies reveal Arnicolide D’s dose-dependent cytotoxicity against cancer cell lines, including nasopharyngeal carcinoma, triple-negative breast cancer, and human colon carcinoma, showcasing its broad-spectrum anticancer potential. Given its multifaceted mechanisms and preclinical efficacy, Arnicolide D warrants further investigation in clinical settings to validate its therapeutic utility against cancer. The evidence presented underscores the need for rigorous pharmacokinetic and toxicological studies to establish safe dosing parameters for future clinical trials.